2013
DOI: 10.1016/j.jpedp.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Assessment of Neglected Diseases in Children: Lymphatic Filariasis and Soil-Transmitted Helminthiasis

Abstract: Objective: To report the prevalence of lymphatic filariasis and intestinal parasitic infections in school-aged children living in a filariasis endemic area and discuss about the therapeutic regimen adopted in Brazil for the large-scale treatment of filariasis. Methods: A cross-sectional study including 508 students aged 5-18 years old, enrolled in public schools within the city of Olinda, Pernambuco. The presence of intestinal parasites was analyzed using the Hoffman, Pons and Janer method on 3 stool samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…MWAKITALU et al [6] reported lymphatic filariasis infection, disease and transmission in Tanga, Tanzania. AGUIAR-SANTOS et al [7] reported lymphatic filariasis and intestinal parasitic infection of school-aged children in Pernambuco, Brazil. In India, microfilariae Wuchereria bancrofti attacked breast woman [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…MWAKITALU et al [6] reported lymphatic filariasis infection, disease and transmission in Tanga, Tanzania. AGUIAR-SANTOS et al [7] reported lymphatic filariasis and intestinal parasitic infection of school-aged children in Pernambuco, Brazil. In India, microfilariae Wuchereria bancrofti attacked breast woman [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recife and its metropolitan region remain as the only endemic region for lymphatic filariasis in Brazil (Freitas et al, 2008;Fontes et al, 2012;Aguiar-Santos et al, 2013). Different factors contribute to this endemism, such as a combination of weather conditions and unplanned urbanization, which result in high population densities of Cx.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the proportion of the population in endemic areas worldwide requiring MDA was 52.4%, with 465.4 million people treated in 37 countries with reported cases. Brazil is a GPELF signatory and conducted MDA between 2003 and 2017 in three municipalities of Pernambuco State: Recife, Olinda, and Jaboatão dos Guararapes, with the exclusive use of diethylcarbamazine (DEC) [7]. Treatment was performed in focal areas, meeting the criteria established by each municipality [8][9][10].…”
Section: Introductionmentioning
confidence: 99%